Knowledge and experience in using 2D and 3D diagnostic imaging among dentists in Surabaya - Ramadhani, Nastiti Faradilla; Nurrachman, Aga Satria; Savitri, Yunita; Asymal, Alhidayati; Mulyani, Sri Wigati Mardi; Widjiastuti, Ira; Luthfi, Muhammad; Valensia, Theodora; Hanun, Hafshah Zhafirah Siri (Indonesian Journal of Dental Medicine, 2024)
Background: Radiography is essential in dentistry for diagnosis and treatment planning, with two-dimensional imaging such as panoramic and periapical radiographs being commonly used. The advancement to three-dimensional imaging, specifically Cone Beam Computed Tomography (CBCT), provides more detailed visualization but remains underutilized due to limited availability and knowledge among dentists in Indonesia. Purpose: This research is aimed to determine the knowledge and experience of using 2D and 3D diagnostic imaging among dentists in Surabaya. Methods: This research is using an observational descriptive study with a cross-sectional design consisting of 100 dentists who are domiciled in Surabaya and registered with PDGI in Surabaya. Results: The result showed that dentists’ knowledge of 2D diagnostic imaging with a good category has a percentage of 18%, quite good category with 49% and poor category with 33%. Meanwhile, the dentists’ knowledge of 3D diagnostic imaging with a good category has a percentage of 9%, quite good category with 36% and poor category with 55%. Around 88% of respondents have referred their patients for panoramic and periapical radiographs, while only about 22% of dentists have referred their patients for CBCT examinations. Conclusion: The knowledge of dentists regarding 2D diagnostic imaging is quite good, while the knowledge of dentists regarding 3D diagnostic imaging is low. The majority of dentists in Surabaya often refer their patients for panoramic and periapical radiographic examinations compared to referring them for CBCT examinations.